Pemanfaatan Aplikasi Canva Sebagai Media Pembelajaran Untuk Meningkatkan Hasil Belajar Peserta Didik Dalam Pak Dan Bp Pada Topik Sepuluh Perintah Allah Sebagai Pedoman Hidup di Kelas IV di SD Swasta Santo Nicholas - Palentinus Tarigan (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
In this digital era, humans are very dependent on technology, especially gadgets that are very popular among various groups. The digital era has provided many conveniences. This article uses a library research method by utilizing articles, journals, books, and internet access as sources. This study aims to use the Canva application to make it easier for users to use applications that can help users to design various types of material online from greeting cards, posters, brochures, infographics to presentation media. Canva is not complicated because it has provided various sizes to templates for the designs that users want, and can be adapted to the purpose of making designs. The conclusions obtained in this research are that the Canva application is one of the media that can support the learning process visually and train visual literacy skills for users in this digital era.